(untitled) (Research, Society and Development, 2022)
Aging is a biological process that happens naturally or early, due to some practices and habits of individuals who have sought ways to delay or attenuate the signs of aging, and the increase in the search for aesthetics and life expectancy, have brought numerous ways that prolong youthful appearance, bringing psychological benefits and quality of life to people. As a result, the techniques and commercial products used have become increasingly safe and effective, with Hyaluronic Acid (HA) being one of the main non-surgical tools that, in addition to being easy to apply and remove, demonstrate a high capacity for hydration, volumization and biocompatibility to the skin, as this is an existing compound in the body. The qualified professional is able to perform this procedure safely, without causing great discomfort to the patient, if performed correctly, the HA will not present risks and will reduce the chances of possible complications. Therefore, this study was an integrative review that aimed to understand the benefits of Hyaluronic Acid, as well as its injectable properties in use in the treatment for facial rejuvenation. The study had a choice of 25 articles, found in several more recent electronic databases, which contributed to the conclusion of the study, which demonstrated the safety and optimal levels of effectiveness of hyaluronic acid in relation to the aesthetic treatment of facial rejuvenation. Complications obtained are difficult, if performed by a qualified professional and if the patient follows the recommended guidelines after performing the procedure.